Enhanced Photocatalytic Activity for Degradation of Organic Dyes Using Magnetite CoFe2O4/BaTiO3 Composite - Hue T. M. Dang; Dung V. Trinh; Nga K. Nguyen; Thi Thanh Thuy Le; Dung D. Nguyen; Hoang V. Tran; M.-H. Phan; Chinh D. Huynh (My University, 2018)
Enhanced Photocatalytic Activity for Degradation of Organic Dyes Using Magnetite CoFe2O4/BaTiO3 Composite
Keywords: CoFe2O4/BaTiO3